HUKUM PIDANA INDONESIA: ULTIMUM REMEDIUM ATAU PRIMUM REMEDIUM - Nur Ainiyah Rahmawati (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2013)
AbstractThe number of misdemeanor cases among people who sued to the realm of the courts in recent times, have seized the attention of the general public. Cases were classified as misdemeanors like theft causes many losses were mostly done by poor people who do not know about the law. Although there anyway because of the economy in a pinch. But in fact, the Indonesian criminal justice system still lacking empirical aspects of implementing the objectives of the law are the rule of law, justice and expediency. All three are still difficult to implement. The purpose of this paper is to review the principles of criminal law as related remedium ultimum reality in society. The method used in this study is a socio-legal approach that is qualitative, based on the literature and cyber media. With this approach, this paper uses two approaches, namely the social approach and normative juridical approach. Writing is concluded that in the present conditions, criminal law no longer reflects the principle ultimum remedium, but rather the principle of Primum remedium. Therefore, the function of law enforcement officers should have been able to use a settlement out of court undertakings to reduce the accumulation of cases in court is also due to limited human resources to handle such cases.Key words: criminal law, the principle of ultimum remedium, law enforcement officers